PERBEDAAN KEMANDIRIAN BELAJAR SISWA LAKI-LAKI DAN PEREMPUAN SMP NEGERI 14 PEKANBARU TP. 2016/2017 - ', Sugiyarni; ', Rosmawati; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to determine the picture of students self regulated leraning of male students and female students, and to know the self regulated learning between male and female students. The hypothesis proposed is : There is difference of self regulated learning between male and female students. The population in this study is all students of class VII at SMPN 14 Pekanbaru academic year 2016/2017. Sampling technique used is Probability Sampling technique by using simple random sampling or random sampling. The instrument used is a questionnaire of self regulated learning. Based on the results of the analysis conducted by using T test (Independent Sample T-Test) obtained the value of sign (2-tailed) of 0.001 <0.05, it can be concluded Ha accepted, which means There is a difference of between male students and Women. Where the self regulated learning of female students is higher than male students.Keywords: Self Regulated Learning, Male Students, Female Students